Heat absorption properties of CuO/TiO2/SiO2 trihybrid nanofluids and its potential future direction towards solar thermal applications - Nur Alya Syamimie, Muzaidi; Mohd Amiruddin, Fikri; Khairul Nizar Syazwan, Wan Salihin Wong; Azfi Zaidi, Mohammad Sof; R., Mamat; Norfatihah, Mohd Adenam; Muhamad Yuzaini Azrai, Mat Yunin; Hasyiya Karimah, Adli (Elsevier Ltd, 2021)
In this study, we investigated the physical properties of CuO/TiO2/SiO2 trihybrid nanofluids. The physical properties that were investigated included density, crystallite size, and surface morphology. The trihybrid nanofluid density was observed to increase at higher volume concentration, with t1 exhibiting the highest density (2.26 gml−1). X-Ray Diffraction (XRD) spectra showed the main diffraction peaks of individual nanoparticles (CuO, TiO2 and SiO2), highlighting the successful formation of trihybrid nanoparticles. The nanofluid's calculated crystallite size showed the formation of smaller trihybrid nanofluid crystallites (5.2 nm) compared to the original nanoparticles. The crystallite size is in good agreement with the SEM surface morphology, which shows the appearance of small particles. The trihybrid solution (t1) had the best thermal properties, based on temperature output, at around 55 °C, as the highest volume concentration of nanofluids was used. The heat absorption of t1 also demonstrated increased temperature output at higher solar radiations with a maximum temperature output at 73 °C under 700 W/m2. This study is the first to report on the thermal properties CuO/TiO2/SiO2 trihybrid nanofluids for future solar thermal application.